2018
DOI: 10.7717/peerj.4775
|View full text |Cite
|
Sign up to set email alerts
|

Intolerance of uncertainty and conditioned place preference in opioid addiction

Abstract: Several personality factors have been implicated in vulnerability to addiction by impacting learning and decision making. One such factor is intolerance of uncertainty (IU), the tendency to perceive uncertain situations negatively and avoid them. Conditioned place preference (CPP), which compares preference for contexts paired with reward, has been used to examine the motivation for both drug and non-drug rewards. However, preference for locations associated with non-drug reward, as well as the potential influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
0
5
0
1
Order By: Relevance
“…Especially for females with SUD who suffer from more negative life events and more uncertainty within their environment, high BIS levels could induce high IU, thus leading to a higher level of depression than the individuals with low BIS levels. Because individuals with high levels of IU show blunted reward responsiveness ( 40 ), the BAS cannot have an indirect impact on depression through IU. On the other hand, the BAS has a close relationship with reward seeking, and individuals with high BAS sensitivity show a high preference for novelty processing and reward dependence ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially for females with SUD who suffer from more negative life events and more uncertainty within their environment, high BIS levels could induce high IU, thus leading to a higher level of depression than the individuals with low BIS levels. Because individuals with high levels of IU show blunted reward responsiveness ( 40 ), the BAS cannot have an indirect impact on depression through IU. On the other hand, the BAS has a close relationship with reward seeking, and individuals with high BAS sensitivity show a high preference for novelty processing and reward dependence ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have suggested that IU plays an important and specific role in the development and maintenance of high levels of worry and generalized anxiety disorder ( 33 , 36 ), an increasing number of researchers regard IU as a transdiagnostic risk factor for a range of psychiatric disorders, such as generalized anxiety disorder, obsessive-compulsive disorder, eating disorders, depression, and SUD ( 37 39 ). For example, several studies have found that compared to healthy individuals, individuals with SUD perceive higher levels of IU ( 12 , 40 ). While the researchers who conducted these studies also suggested that although IU is a feature of SUD, it may not play a unique role.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intolerance of uncertainty predicts the extent of post-traumatic stress symptoms associated with negative stressful life events (59). There is also a strong relationship between intolerance of uncertainty and addictive behavior, and patients treated with opioids have higher intolerance of uncertainty (60). Therefore, the preliminary findings of this study indicate that there may be a complex relationship among the three variables, and we construct the relationship model among them.…”
Section: Discussion the Relationship Between The Dimensionsmentioning
confidence: 84%
“…Por su parte, la intolerancia a la incertidumbre es definida como una tendencia a percibir las situaciones inciertas y ambiguas como negativas, desagradables, inaceptables y amenazantes, independientemente de la probabilidad de que ocurran, lo que les lleva a reaccionar ante ellas de manera intensa y negativa a nivel emocional, cognitivo y conductual, así como a evitarlas (Morriss y McSorley, 2019;Radell et al, 2018;Rodgers et al, 2019;Roma y Hope, 2017). Asimismo, la dificultad para tolerar la incertidumbre supone cierto riesgo al incrementar la probabilidad de adopción de conductas de riesgo dirigidas a aliviar las emociones angustiosas o desagradables (Sadeh y Bredemeier, 2019).…”
Section: Introductionunclassified